(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
We are living in an era in which globalization and digital transformation are fundamentally reshaping human cognition, including the system of values within society. In particular, the rapid influx of diverse information flows and elements of foreign cultures through modern technologies has led to profound transformational processes in young people’s worldviews and spiritual identity. Under these circumstances, harmonizing national identity and historical memory with the continuously evolving dynamics of socio-cultural values has become an urgent priority. University students, as the intellectual driving force and future leaders of society, are among the first to embrace these changes. Therefore, ensuring the appropriate direction of the transformation of students’ spiritual worldview and conducting an in-depth scientific analysis of the role and influence of the evolving dynamics of socio-cultural values within this complex process constitute not only a pedagogical and educational imperative but also a significant socio-strategic challenge.